2017
DOI: 10.1002/pssa.201600657
|View full text |Cite
|
Sign up to set email alerts
|

Chemical lift‐off process for nitride LEDs from an Eco‐GaN template using an AlN/strip‐patterned‐SiO2 sacrificial layer

Abstract: In this research, a nitride light‐emitting diode (LED) fabricated on an electroplated Cu substrate can be removed from a GaN/sapphire (Eco‐GaN) template by conducting the chemical lift‐off (CLO) process using an AlN/strip‐patterned‐SiO2 intermediate sacrificial layer. The regrowth GaN epilayer deposited on AlN/patterned SiO2/Eco‐GaN can achieve a high crystal quality via the epitaxial lateral overgrowth process. To etch the patterned SiO2 and AlN layers, the HF and 80 °C‐KOH solutions were used, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The growth of the 170‐µm‐thick n‐type GaN:Si layer at 1090 °C and 0.7 µm min −1 from the mixed‐source (Ga + Si) contained in the second boat progresses. Figure (e) and (f) show the schematic drawing and SEM image, respectively, of the epilayer connected by the trapezoidal pillar arms grown along the direction originating from the top of the n‐type GaN pyramids with increasing the growth time in the growth of the 170‐µm‐thick n‐type GaN:Si layer. The scale bar is 20 µm.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The growth of the 170‐µm‐thick n‐type GaN:Si layer at 1090 °C and 0.7 µm min −1 from the mixed‐source (Ga + Si) contained in the second boat progresses. Figure (e) and (f) show the schematic drawing and SEM image, respectively, of the epilayer connected by the trapezoidal pillar arms grown along the direction originating from the top of the n‐type GaN pyramids with increasing the growth time in the growth of the 170‐µm‐thick n‐type GaN:Si layer. The scale bar is 20 µm.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…A vertical‐type LED with one electrode on each side by metallization on both the upper and bottom sides of the single chip can be obtained by detaching from the substrate using a laser lift‐off (LLO) or a chemical lift‐off (CLO) method in the chip fabrication process and by direct growth of epilayer on Si, SiC, GaN, or GaAs substrates, respectively. These vertical‐type LEDs have higher efficiencies than that of lateral‐type ones because of several advantages such as i) a low operation voltage due to a very low serial resistance, ii) excellent heat dissipation due to high thermal conductivity, iii) good assurance by uniform light emission, and iv) elimination of electrostatic discharge . The LED hybrid technology obtained by adding the packaging steps to emit light also has problems such as an increment in the production cost.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned above, the laser lift-off technique is one way to fabricate vertical structure LEDs, but will lead to additional defects and a rough surface to devices resulting from the high energy laser irradiation [40][41][42], while chemical lift-off will not damage the interface between epilayer and substrate [43]. Recently, researches have been carried out for chemical lift-off of GaN using various interlayers [43][44][45][46][47][48]106,107,[114][115][116][117][118][119][120]. Lin et al demonstrated the CLO process of InGaN-based LEDs grown on triangle-shaped and truncated-triangle-striped patterned sapphire substrates employing AlN as a sacrificial layer [115,116].…”
Section: Ga 2 O 3 Sacrificial Layermentioning
confidence: 99%
“…As mentioned above, the laser lift-off technique is one way to fabricate vertical structure LEDs, but will lead to additional defects and a rough surface to devices resulting from the high energy laser irradiation [40,41,42], while chemical lift-off will not damage the interface between epilayer and substrate [43]. Recently, researches have been carried out for chemical lift-off of GaN using various interlayers [43,44,45,46,47,48,106,107,114,115,116,117,118,119,120]. Lin et al demonstrated the CLO process of InGaN-based LEDs grown on triangle-shaped and truncated-triangle-striped patterned sapphire substrates employing AlN as a sacrificial layer [115,116].…”
Section: Epitaxy Of Gan On β-Ga2o3mentioning
confidence: 99%
“…However, using KOH as etchant might also damage the GaN grown on AlN. Horng et al reported the vertical structure nitride LED fabricated on Cu substrate via CLO process employing an AlN/strip-patterned-SiO 2 interlayer as a sacrificial layer [117]. In addition, the direct growth of GaN on CrN and ZnO has been demonstrated, and the CLO process to detach the GaN epilayer has been realized using CrN and ZnO as sacrificial layers [43,44,45,46,47,48].…”
Section: Epitaxy Of Gan On β-Ga2o3mentioning
confidence: 99%